2012
DOI: 10.1371/journal.pone.0049839
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobiosis Induced State Transition: A Non Photochemical Reduction of PQ Pool Mediated by NDH in Arabidopsis thaliana

Abstract: BackgroundNon photochemical reduction of PQ pool and mobilization of LHCII between PSII and PSI are found to be linked under abiotic stress conditions. The interaction of non photochemical reduction of PQ pool and state transitions associated physiological changes are critically important under anaerobic condition in higher plants.Methodology/FindingsThe present study focused on the effect of anaerobiosis on non-photochemical reduction of PQ pool which trigger state II transition in Arabidopsis thaliana. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…The strong increase of the OJ amplitude in anoxia reflects a block of electron transport in PSII due to highly reduced state of the PQ pool, whereas the following dip is caused by the transient re‐oxidation of the PQ pool by PSI and/or by transient accumulation of the fluorescence quencher P 680 + . A similar dip was earlier observed in plant leaves exposed to anoxia (Nellaepalli et al ). The appearance of the additional fast component with a lifetime of circa 50 μs was first evidenced in DCMU‐treated S deprived C. reinhardtii cells (Antal et al ).…”
Section: Discussionsupporting
confidence: 88%
“…The strong increase of the OJ amplitude in anoxia reflects a block of electron transport in PSII due to highly reduced state of the PQ pool, whereas the following dip is caused by the transient re‐oxidation of the PQ pool by PSI and/or by transient accumulation of the fluorescence quencher P 680 + . A similar dip was earlier observed in plant leaves exposed to anoxia (Nellaepalli et al ). The appearance of the additional fast component with a lifetime of circa 50 μs was first evidenced in DCMU‐treated S deprived C. reinhardtii cells (Antal et al ).…”
Section: Discussionsupporting
confidence: 88%
“…Flushing nitrogen gas over leaf discs led to increased Fo-Fj phase in both lines. This effect has previously been attributed to induced fermentative metabolism and over-reduction of the chloroplast plastoquinone pool [38]. Most importantly, while suppression of the Fi-Fm rise by MV was still detected in the wild type, it was absent in rcd1 (Fig 4C, right panel, Fig.…”
Section: Resultssupporting
confidence: 56%
“…An analysis of the OJIP fluorescence curves also suggested a higher chlororespiration activity during darkness. Nellaepalli et al () reported that the non‐photochemical reduction of the plastoquinone pool associated with chlororespiration in Arabidopsis thaliana induced alterations in the shape of the OJIP fluorescence transient and a decrease in the P peak. In our study, when A. erici was maintained in darkness, we found a decrease in fluorescence emission from J to P that was accompanied by the development of a dip between the I and P points (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The STN7 kinase involved in LHCII phosphorylation is activated when reduced PQ binds to its Q o binding site on the cytochrome b 6 f complex (Vener et al , Zito et al , Bellafiore et al ). Interestingly, Nellaepalli et al () have proposed that an increase in chlororespiratory NADH dehydrogenase activity in Arabidopsis thaliana under anaerobiosis can trigger non‐photochemical reduction of the PQ pool, leading to state transitions through activation of the STN7 kinase. An immunoblot analysis carried out on A. erici showed that the level of LHCII phosphorylation was higher in cells kept in darkness than in cells kept under light (Fig.…”
Section: Discussionmentioning
confidence: 99%